Mortality of leaf-cutting ants with salicylic acid - Fazam, Juliana Chiquetti; Shimizu, Gabriel Danilo; Almeida, Júlio Cesar de; Pasini, Amarildo (Semina: Ciências Agrárias, 2021)
Strategies for the control of leaf-cutting ants have mainly involved granular baits based on fipronil and sulfluramid as active ingredients, which are commonly coated with attractive citrus-based substances. Their constant use and the lack of alternatives in the market may favor the perception of these substances by ants, causing rejection for foraging and consequent difficulty in their control. In this respect, this study examined the mortality of leaf-cutting ants of the genera Atta and Acromyrmex subjected to direct application with dry powders, in laboratory conditions. As a preliminary treatment, a commercial antiseptic talc powder (C. A. P. T.) was used, followed by isolated treatments that corresponded to its components with potential insecticidal action, namely, salicylic acid, sulfur, boric acid, zinc oxide, in addition to an inert talc powder (Quimidrol®) as the control. For each treatment, 40 (worker) ants, whose activity was reduced due to remaining in a refrigerator prior to the treatment, were placed in transparent crystal polystyrene ('Gerbox' type) and were sprinkled with a salt shaker. The ants were kept at 25 ± 2 °C, under a 12-h photophase, and cumulative mortality was recorded every 24 h, considering dead ants as those that were unable to maintain the natural position of their body, i.e., even dying ants were considered dead when they exhibited no reaction when touched by a paintbrush. When sprinkled on ants, C. A. P. T. causes 40% mortality in both species 24 h after application. Subsequent studies of the components of this commercial product have found that when sprinkled on both Atta sexdens rubropilosa and Acromyrmex crassispinus, salicylic acid causes 100% mortality of workers in the first 24 h. This result provides a new prospect of control through a low environmental-impact product, representing an alternative for control in nests in the field that can contribute to the integrated control of ants.